Astragaloside II Ameliorated Podocyte Injury and Mitochondrial Dysfunction in Streptozotocin-Induced Diabetic Rats - Su, Jun; Gao, Chongting; Xie, Ling; Fan, Ying; Shen, Yilan; Huang, Qunwei; Wang, Niansong; Xu, Youhua; Yang, Nizhi; Gui, Dingkun (Frontiers in Pharmacology, 2021)
Astragaloside II (AS II), a novel saponin purified from Astragalus membranes, has been reported to modulate the immune response, repair tissue injury and prevent inflammatory response. However, the protective effects of AS II on podocyte injury in diabetic nephropathy (DN) have not been investigated yet. In this study, we aimed to investigate the beneficial effects of AS II on podocyte injury and mitochondrial dysfunction in DN. Diabetes was induced with streptozotocin (STZ) by intraperitoneal injection at 55 mg/kg in rats. Diabetic rats were randomly divided into four groups, namely, diabetic rats, diabetic rats treated with Losartan (10 mg·kg-1·d-1) or AS II (3.2 mg·kg-1·d-1 and 6.4 mg·kg-1·d-1) for 9 weeks. Normal Sprague-Dawley rats were chosen as nondiabetic control group. Urinary albumin/creatinine ratio (ACR), biochemical parameters, renal histopathology and podocyte apoptosis and morphological changes were evaluated. Expression of mitochondrial dynamics-related and autophagy-related proteins, such as Mfn2, Fis1, P62 and LC3, as well as Nrf2, Keap1, PINK1 and Parkin were examined by immunohistochemistry, western blot, and real-time PCR, respectively. Our results indicated that AS II ameliorated albuminuria, renal histopathology and podocyte foot process effacement and podocyte apoptosis in diabetic rats. AS II also partially restored the renal expression of mitochondrial dynamics-related and autophagy-related proteins, including Mfn2, Fis1, P62 and LC3. AS II also increased the expression of PINK1 and Parkin that associated with mitophagy in diabetic rats. Moreover, AS II facilitated antioxidative stress ability via increasing Nrf2 expression and decreasing Keap1 protein level. These results suggested that AS II ameliorated podocyte injury and mitochondrial dysfunction in diabetic rats partly through regulation of Nrf2 and PINK1 pathway. These important findings might provide an innovative therapeutic strategy for the treatment of DN.